1981
DOI: 10.1111/j.1471-4159.1981.tb01697.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intravenous Administration of d‐Lysergic Acid Diethylamide on Subsequent Protein Synthesis in a Cell‐Free System Derived from Brain

Abstract: An initiating cell-free protein synthesis system derived from brain was utilized to demonstrate that the intravenous injection of d-lysergic acid diethylamide (LSD) to rabbits induced a transient inhibition of translation following a brief stimulatory period. Subfractionation of the brain cell-free system into postribosomal supernatant (PRS) and microsome fractions demonstrated that LSD in vivo induced alterations in both of these fractions. In addition to the overall inhibition of translation in the cell-free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1981
1981
1991
1991

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Recent studies in our laboratory have shown that the reduction in brain protein synthesis by either LSD or elevated ambient temperature treatment is accompanied by selective effects on the synthesis of particular brain proteins in both in vivo (Freedman et al, 1981) and homologous cell-free protein synthesis systems (Cosgrove et al, 1981). For example, LSD and direct heat treatment increased the relative labeling of a 75K and 95K brain protein and induced a decrease in the relative labeling of a 55K protein (Freedman et al, 1981;Cosgrove et al, 1981). These differential labeling effects on brain proteins appear to be caused by hyperthermia induced by either LSD or elevated ambient temperature.…”
Section: -75\mentioning
confidence: 99%
“…Recent studies in our laboratory have shown that the reduction in brain protein synthesis by either LSD or elevated ambient temperature treatment is accompanied by selective effects on the synthesis of particular brain proteins in both in vivo (Freedman et al, 1981) and homologous cell-free protein synthesis systems (Cosgrove et al, 1981). For example, LSD and direct heat treatment increased the relative labeling of a 75K and 95K brain protein and induced a decrease in the relative labeling of a 55K protein (Freedman et al, 1981;Cosgrove et al, 1981). These differential labeling effects on brain proteins appear to be caused by hyperthermia induced by either LSD or elevated ambient temperature.…”
Section: -75\mentioning
confidence: 99%
“…In previous reports, it has been shown that hyperthermia generated by elevation of ambient temperature or intravenous injection of LSD induces a transient inhibition of protein synthesis (19,20,(29)(30)(31)(32) and an induction of synthesis of a 74-kDa heat shock protein in various regions of the mammalian brain (8, 9, 11-13, 15, 16). In the visual system, the present results indicate that the 74-kDa heat shock protein undergoes axonal transport from neuronal cell bodies in the retina to synaptic termini in the superior colliculus, where maximal labeling of the protein was evident by 30 days after intraocular injection of [35S]methionine.…”
Section: Discussionmentioning
confidence: 99%
“…Animals that were injected with LSD exhibited rectal temperatures of 42.6 ± 0.4°C 1 hr after drug administration. When required, the hyperthermic response that was normally induced by LSD could be blocked by keeping rabbits in a cold room at 4°C (19,20). Under these conditions, body temperature remained at 39.6°C; however, the behavioral effects of the drug were still apparent.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that the system translates a wide spectrum of endogenous brain messenger RNAs. In the accompanying report (Cosgrove et al, 1981), data are presented that indicate that following intravenous administration of LSD, cell-free translation systems prepared from drugtreated animals exhibit a reduced capacity for protein synthesis. These results are similar to those obtained in vivo Brown, 1976, 1977;Freedman et al, 1981).…”
Section: J W Cosgrove a N D I R Brownmentioning
confidence: 99%